2019
DOI: 10.1002/met.1869
|View full text |Cite
|
Sign up to set email alerts
|

Variability of integrated precipitable water over India in a warming climate

Abstract: Changes in precipitation patterns as a result of increased atmospheric water vapour in a warming environment over the Indian region have been reported in the past few decades. However, these studies have not focused much on exploring the changes in atmospheric water vapour in a changing climate. The present study focuses on examining the variability of integrated precipitable water (IPW) over the Indian region derived from the Modern Era Retrospective‐Analysis for Research and Application (MERRA 2) model in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…For example, Jade et al (2019) 19 showed that the interannual variation of PWV is about 9–22% for southern India, 9–19% for Himalaya and about 3–10% for northeast India. Mishra (2019) 20 showed a positive trend of about 1.69% dec −1 in PWV for the period 1980–2018 in India. Similarly, Jindal et al (2020) 21 found positive trends in PWV at different locations in India (about 1.663% per year and 0.580% per year over Hyderabad and Delhi, respectively) during the period 2003–2011.…”
Section: Introductionmentioning
confidence: 97%
“…For example, Jade et al (2019) 19 showed that the interannual variation of PWV is about 9–22% for southern India, 9–19% for Himalaya and about 3–10% for northeast India. Mishra (2019) 20 showed a positive trend of about 1.69% dec −1 in PWV for the period 1980–2018 in India. Similarly, Jindal et al (2020) 21 found positive trends in PWV at different locations in India (about 1.663% per year and 0.580% per year over Hyderabad and Delhi, respectively) during the period 2003–2011.…”
Section: Introductionmentioning
confidence: 97%
“…Another source of data is provided by reanalysis models, such as CAMS or MERRA-2 (Gueymard and Yang 2020; Kosmopoulos et al 2018). Similarly, water vapor information can be retrieved from the Global Ozone Monitoring Experiment-2 (GOME-2), the Scanning Imaging Absorption Spectrometer for Atmospheric Cartography (SCIAMACHY), and MODIS spaceborne instruments (Beirle et al 2018;, or from reanalysis models (Mishra 2019). Although AOD and PW are derived mostly from polar-orbiting satellites, several retrievals are developed with geostationary satellites, such as Himawari-8, the Geostationary Operational Environmental Satellite (GOES), and Meteosat (Kaufman, Tanré, and Boucher 2002).…”
Section: Aerosols and Water Vapormentioning
confidence: 99%
“…The WBC estimates evapotranspiration using the Blaney-Criddle formula [8]. This empirical formula is based on data from the arid climatic conditions of the United States and takes into account the sunshine hours and temperature.…”
Section: Estimation Of Evaporation Evapotranspiration and Infiltrationmentioning
confidence: 99%
“…[5][6][7]. The interference to the hydrological cycle at one stage can lead to serious consequences at some other stage due to the strong interdependency between the stages of the cycle [8]. India, having predominantly the rural and agricultural society, is no more exempted from the issue of water scarcity, security, and spatial non-uniformity in the water distribution [9][10][11].…”
Section: Introductionmentioning
confidence: 99%